2022
DOI: 10.1177/21677026221078309
|View full text |Cite
|
Sign up to set email alerts
|

Does Objectively Measured Social-Media or Smartphone Use Predict Depression, Anxiety, or Social Isolation Among Young Adults?

Abstract: Despite a plethora of research, the link between digital-technology use and psychological distress among young adults remains inconclusive. Findings in this area are typically undermined by methodological limitations related to measurement, study design, and statistical analysis. Addressing these limitations, we examined the prospective, within-persons associations between three aspects of objectively measured digital-technology use (duration and frequency of smartphone use, duration of social-media use) and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…The main theme of Anxiety-Disorder (0.79, 0.64) was determined to have a relationship with Online-Games, Psychopathology, Academic-Performance, Addictive-Behavior, Body-Image, Boredom-Proneness, Human-Computer-Interaction and Occupational-Experience . These studies on Online-Games ( Alhamoud et al, 2022 ), Psychopathology ( Wolniewicz et al, 2020 ), Academic-Performance ( Sayed et al, 2022 ), Addictive-Behavior ( Kuru and Celenk, 2021 ), Body-Image ( Hawes et al, 2020 ), Boredom-Proneness ( Wolniewicz et al, 2020 ), Human-Computer-Interaction ( Sewall et al, 2022 ), and Occupational-Experience ( Zamora et al, 2021 ) exemplify the sub-themes in the Anxiety-Disorder cluster network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main theme of Anxiety-Disorder (0.79, 0.64) was determined to have a relationship with Online-Games, Psychopathology, Academic-Performance, Addictive-Behavior, Body-Image, Boredom-Proneness, Human-Computer-Interaction and Occupational-Experience . These studies on Online-Games ( Alhamoud et al, 2022 ), Psychopathology ( Wolniewicz et al, 2020 ), Academic-Performance ( Sayed et al, 2022 ), Addictive-Behavior ( Kuru and Celenk, 2021 ), Body-Image ( Hawes et al, 2020 ), Boredom-Proneness ( Wolniewicz et al, 2020 ), Human-Computer-Interaction ( Sewall et al, 2022 ), and Occupational-Experience ( Zamora et al, 2021 ) exemplify the sub-themes in the Anxiety-Disorder cluster network.…”
Section: Resultsmentioning
confidence: 99%
“…The main theme of Social-Media-Addiction (0.93, 0.5) was determined to have a strong relationship with Self-Regulation, Social-Isolation, Deep-Learning, Emerging-Adults, Postpartum-Depression, Race/Ethnicity, Racial-Discrimination, and Schizophrenia themes. These studies on Self-Regulation (Akıl et al, 2022), Social-Isolation (Sewall et al, 2022), Deep-Learning (Kim et al, 2022), Emerging-Adults (Cano et al, 2021), Postpartum-Depression (Shatte et al, 2020), Race/Ethnicity (Nereim et al, 2022), Racial-Discrimination (Pan et al, 2021), and Schizophrenia (Li et al, 2020) could be listed to support the emergent sub-themes in the Social-Media-Addiction cluster network. The main theme of Internet-Addiction (0.86, 0.93) was found to be related to Students, Teachers, Cyberbullying-Victimization, Disordered-Sleep, Family-Factors, Impulsivity, K-12-Education, and Self-Efficacy themes.…”
Section: Period 3 (2020-2022)mentioning
confidence: 99%
“…Thus, we cannot be certain here that all students here are being scored on the same metric/number of devices (i.e., some students may have higher objective screen time values because they spend lots of time on their MacBook whereas others may be spending lots of time on an iPhone specifically). Future research seeking to employ objective screen time should consider querying whether this setting turned on, and if so, what other devices the student has linked to their Apple ID that would be tracked and/or using recently developed protocols for uploading screen time screenshots that capture this setting (Sewall et al, 2022). Second, as with all cross-sectional research, it is important to remember that the present study cannot be used for causal inference and does not tell us definitively what the drivers of the observed associations are.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, objective measures provide a clearer lens through which to understand digital technology and mental health associations ( Parry et al, 2021 ), which is integral to addressing methodological limitations presented by previous research ( Kaye et al, 2020 ). In fact, those few studies using objective measures of digital media engagement have little evidence of sizable or robust associations with mental health ( Rozgonjuk et al, 2018 ; Hodes and Thomas, 2021 ; Sewall et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…5,15 Such inaccuracy in reporting SNS use may be significant in studying associations with well-being. Prior studies found that self-reported SNS data may be systematically biased by use patterns, such as the volume of smartphone use, 15,16 which are crucial to the phenomenon under investigation. Indeed, a recent study found that the correlations between estimated use and depression, loneliness, and life satisfaction were consistently stronger than the correlations between reported actual use and these outcomes.…”
Section: Measurement Of Sns Smartphone App Usementioning
confidence: 99%